Suicidal Death Autopsy Analysis at Dhaka Medical College (Bangladesh Medical Journal, 2012)
A cross sectional study was carried out at the department of Forensic Medicine in Dhaka Medical College during the period of January 2008 to December 2009. Data were collected from 3rd copy of the post mortem reports which were preserved in the department of Forensic Medicine with the verbal consent of the doctors who performed autopsy report. During this period total 5114 autopsies were conducted. Out of this 970 cases (19%) were suicidal in nature. It was noticed that all suicidal deaths occurred from 10 years to all age group respectively, but top amongst age group of suicidal deaths occurred in between 21 to 30 years of people. Suicidal deaths are more common in female than male. Suicidal deaths due to hanging is highest, next common causes of death due to organophosphorus compund poisoning. Suicidal deaths by hanging is more in female than male but in poisoning cases male are more lvictimised than female. Objectives of our study are to see the occurrence and methods of suicidal death. DOI: http://dx.doi.org/10.3329/bmj.v40i1.9957 BMJ 2011; 40(1): 18-21